Determinasi Kepuasan Mahasiswa terhadap Layanan Aplikasi BRImo di Kota Semarang - Rizqi Sukya Arrohmah; Prihatiningsih; Septian Yudha Kusuma (Jurnal Keuangan dan Perbankan Syariah, 2025)
Purpose: This study aims to analyze the effect of convenience, security, and service quality on customer satisfaction among student users of BRImo in Semarang City, both simultaneously and partially. Design/methodology/approach: This research employed a quantitative approach using purposive sampling. The population consisted of students in Semarang City who used BRImo, with a total of 152 respondents. Primary data were collected through questionnaires distributed via Google Form. Data analysis was conducted using SPSS 26 with multiple linear regression, supported by the F-test, t-test, and coefficient of determination (R²). Research Findings: The findings indicate that convenience, security, and service quality partially have a significant effect on customer satisfaction among student BRImo users in Semarang City. Service quality shows the strongest influence on customer satisfaction, although several issues remain such as server disruptions and transaction costs. Security is the second most influential factor, supported by layered features such as OTP and biometric authentication. Convenience has the third strongest influence due to BRImo’s simple interface and complete features. Contribution/Originality/Novelty: This study contributes empirical evidence regarding the key determinants of customer satisfaction in digital banking services, particularly among student users. The novelty of this research lies in its focus on the student segment as a specific user group of BRImo, providing insights for improving service quality, security systems, and user convenience in mobile banking applications.